2018
DOI: 10.2147/idr.s160720
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of plasmid-mediated quinolone resistance and ESBL-production in <em>Enterobacteriaceae </em>isolated from urinary tract infections

Abstract: Introductionβ-lactam and fluoroquinolone antibiotics are usually used for the treatment of urinary tract infections (UTIs). The aim of this study was to determine the prevalence of plasmid-mediated quinolone resistance (PMQR) and extended spectrum β-lactamases (ESBLs) in Enterobacteriaceae isolated from UTIs.Materials and methodsTwo hundred and nineteen samples of Enterobacteriaceae isolated from UTIs were collected in the Northwest of Iran. Antimicrobial susceptibility testing was determined by the disk diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
50
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 27 publications
15
50
6
1
Order By: Relevance
“…In the current study, ESBL-producing Enterobacteriaceae was more than half of the isolates. In contrast to our results, Azargun et al (2018) reported the 34.2% of their isolates were ESBL-producing and K. pneumoniae was 53.5% then E. coli was 33.8% [32]. However Rao et al (2014) found 61.4% of ESBL production among E. coli and 46.2% among K. pneumoniae [33].…”
Section: Discussioncontrasting
confidence: 98%
“…In the current study, ESBL-producing Enterobacteriaceae was more than half of the isolates. In contrast to our results, Azargun et al (2018) reported the 34.2% of their isolates were ESBL-producing and K. pneumoniae was 53.5% then E. coli was 33.8% [32]. However Rao et al (2014) found 61.4% of ESBL production among E. coli and 46.2% among K. pneumoniae [33].…”
Section: Discussioncontrasting
confidence: 98%
“…However, the isolates were most resistant to Nalixidic acid and were least resistant to Imipenem, Levofloxacin and Norfloxacin. This partially agrees with a similar study carried out in Azerbaijan and Iran on ESBL-PMQR co-carriage where resistance to Nalixidic acid was highest (68.5%) closely followed by resistance to Levofloxacin (55%) and Norfloxacin (65%) (Azargun et al, 2018). The injudicious and common use of Nalixidic acid in comparison to other fluroquinolones, Levofloxacin and Norfloxacin could be the reason for such high resistance to Nalixidic acid in this region.…”
Section: Discussionsupporting
confidence: 91%
“…The clinical relevance of our results is that ciprofloxacin is commonly subscribed to treat UTIs. It is estimated that around 150 million UTI cases are diagnosed each year and about 75% are caused by E. coli [22]. Ciprofloxacin concentrations used in this study demonstrate tissue concentrations during a per os therapy [30].…”
Section: Discussionmentioning
confidence: 96%
“…The reason of this abundance can have evolutionary advantage against other qnr determinants. This theory is supported by the fact that qnrB is often associated with other resistance genes, such as bla CTX-M-15 , bla CTX-M-14 , and aac(6′)-Ib-cr [22], which can cause multiresistance and facilitate dissemination of resistant strains [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation